REGISTER BAHASA PERANCIS PEMANDUAN PENYUSUNAN PROGRAM PERJALANAN WISATA - Muhammad Hasyim; Prasuri Kuswarini; Masdiana Masdiana (Jurnal Ilmiah Hospitality, 2022)
A tour program is a program designed to promote tourist destinations to tourists. The preparation of an effective tour program will produce a positive effect that makes tourists intend to visit the site following the tour program offered. This paper aims to discuss the registration of the French language in guiding the preparation of tourism travel programs for tourism stakeholders in Makassar. The method used in this paper is a literature study by compiling a list of French-language tours, and the list becomes a reference in the preparation of tourist trips for tourism stakeholders. The activity of preparing the travel program was carried out through a Focus Group Discussion (FGD) by inviting 20 stakeholder respondents as participants. In the paper's conclusion, it says that the stakeholders can make a French tour program after getting training on how to introduce the French language and a program tour guide module.